The genius life : heal your mind, strengthen your body, and become extraordinary - Lugavere, Max (HarperWave, an imprint of HarperCollins Publishers, 2020)
The author of the New York Times bestselling Genius Foods is back with a lifestyle program for resetting your brain and body to its "factory settings," to help fight fatigue, anxiety, and depression and to optimize cognitive health for a longer and healthier life. The human body was honed under conditions that no longer exist. The modern world has changed dramatically since our days as hunter gatherers, and it has caused widespread anxiety, stress, and disease, leaving our brains in despair. But science proves that the body and brain can be healed with the intervention of lifestyle protocols that help us to regain our cognitive birthright. In The Genius Life, Lugavere expands the Genius Foods plan, which focused on nutrition and how it affects brain health, and expands it to encompass a full lifestyle protocol. We know now that the health of our brains- including our cognitive function and emotional wellness- depend on the health of our gut, endocrine, cardiac and nervous systems as there is a constant feedback loop between all systems. Drawing on globe-spanning research into circadian biology, psychology, dementia prevention, cognitive optimization, and exercise physiology, The Genius Life shows how to integrate healthy choices in all aspects of our daily routines: eating, exercising, sleeping, detoxing, and more to create a healthy foundation for optimal cognitive health and performance.